2014
DOI: 10.1177/0269216314522105
|View full text |Cite
|
Sign up to set email alerts
|

Increasing anticholinergic burden and delirium in palliative care inpatients

Abstract: An increase in Anticholinergic Risk Scale from admission was associated with delirium in palliative care inpatients. While additional study is needed, anticholinergic burden should be increased cautiously in palliative inpatients, and those with increases should be closely followed for delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 25 publications
4
59
0
1
Order By: Relevance
“…Our finding that anticholinergic drug exposure measured with the ARS is associated with delirium, is in agreement with the results of previous studies performed in critically ill patients (Wolters et al 2015), palliative care patients (Zimmerman et al 2014), patients with Parkinson's disease (Crispo et al 2016) and older nursing home residents (Landi et al 2014). Also, previous studies found no association between anticholinergic drug exposure, measured with the ACB or the Anticholinergic Drug Scale, and delirium in older hospitalized patients (Moorey et al 2016;Campbell et al 2011;Wolters et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that anticholinergic drug exposure measured with the ARS is associated with delirium, is in agreement with the results of previous studies performed in critically ill patients (Wolters et al 2015), palliative care patients (Zimmerman et al 2014), patients with Parkinson's disease (Crispo et al 2016) and older nursing home residents (Landi et al 2014). Also, previous studies found no association between anticholinergic drug exposure, measured with the ACB or the Anticholinergic Drug Scale, and delirium in older hospitalized patients (Moorey et al 2016;Campbell et al 2011;Wolters et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore effective treatments should be accessible and amenable to administration with minimal burden, thus ensuring no increased distress to the patient. A medication profile review and an increase in the Anticholinergic Risk Scale will assist in identifying potential deliriogenic medications that can be dose-reduced or discontinued (50,51). Apart from the imminently dying context (last hours of life), an opioid switch (with a reduction in opioid equianalgesic dose by 30-50%) also may be appropriate if signs of opioid-induced neurotoxicity are present, although there remains a lack of high level evidence for this strategy in delirious patients (52,53).…”
Section: Delirium Reversibility In End-of-life Carementioning
confidence: 99%
“…For example, delirium in palliative care patients is rarely attributed to medications,21 despite the fact that increasing numbers of symptom-specific medications as death approaches have been shown to be the biggest contributing factor to anticholinergic load 2 22. At the very end of life, such medication combinations are even more likely to lead to clinically apparent drug interactions 23…”
Section: Introductionmentioning
confidence: 99%